Sharia Marketing Strategy in Facing Business Competition (Case Study at Yen Collection Strore Bukittinggi) - NURMEILIA, RAHMI (Sharia Business Management UIN Raden Intan Lampung, 2023)
AbstractYen Collection shop located at Jalan Sutan Syahrir No.56 A6/A5 Tarok dipo Bukittinggi sells school uniforms. Basically, this shop is still not good in terms of customer service, the price of its products is very high compared to competitors and they are still lacking in promotion. The purpose of this study is to find out how the sharia marketing strategy used by Yen Collection Bukittinggi shop owners to compete with their competitors. This research uses a qualitative descriptive method. The methods used for data collection are interviews, observation, and documentation. Data obtained from Yen Collection consumers, Yen Collection owners and employees. The data obtained is then analyzed using a SWOT analysis strategy using the IFAS, EFAS and SWOT matrix. Based on the analysis conducted by the author, the results showed that the Yen Collection Bukittinggi store uses a sharia marketing strategy in facing business competition, the first marketing mix strategy is divided into seven elements such as price, process, product, promotion, location or place, people or human resources and physical facilities or physical evidence. The ultimate goal of this strategy is to get a lot of consumers, retain existing consumers and win the competition with competitors. The second strategy, by implementing Islamic marketing, namely sharia marketing principles such as theoretical, ethical, realistic and humanistic. In addition, the application of sharia marketing characteristics includes Theistic (Rabbaniyyah), Ethical (Akhlaqiyyah), Realistic (Al-Waqi'iyyah) and Humanistic (Al-Insaniyyah). In the research results with SWOT analysis, EFAS and IFAS matrices and cartesian diagrams, the Yen Collection Bukittinggi store is located in quadrant I that has a status (+,+), namely positive strength positive opportunity. This place shows the position of the store has great strengths and excellent opportunities. For this reason, the recommended strategy is aggressive to enable continuous expansion, greater growth, and maximum progress.Keywords: Sharia Marketing Strategy, Business Competition, SWOT Analysis